Math, asked by VIBHA1212, 3 months ago

solve for x (ii)17(2-x)-5(x+12)=8/1-7x​

Answers

Answered by gpm18
3

Answer:

Simplifying

17(2 + -1x) + -5(x + 12) = 8(1 + -7x)

(2 * 17 + -1x * 17) + -5(x + 12) = 8(1 + -7x)

(34 + -17x) + -5(x + 12) = 8(1 + -7x)

Reorder the terms:

34 + -17x + -5(12 + x) = 8(1 + -7x)

34 + -17x + (12 * -5 + x * -5) = 8(1 + -7x)

34 + -17x + (-60 + -5x) = 8(1 + -7x)

Reorder the terms:

34 + -60 + -17x + -5x = 8(1 + -7x)

Combine like terms: 34 + -60 = -26

-26 + -17x + -5x = 8(1 + -7x)

Combine like terms: -17x + -5x = -22x

-26 + -22x = 8(1 + -7x)

-26 + -22x = (1 * 8 + -7x * 8)

-26 + -22x = (8 + -56x)

Solving

-26 + -22x = 8 + -56x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '56x' to each side of the equation.

-26 + -22x + 56x = 8 + -56x + 56x

Combine like terms: -22x + 56x = 34x

-26 + 34x = 8 + -56x + 56x

Combine like terms: -56x + 56x = 0

-26 + 34x = 8 + 0

-26 + 34x = 8

Add '26' to each side of the equation.

-26 + 26 + 34x = 8 + 26

Combine like terms: -26 + 26 = 0

0 + 34x = 8 + 26

34x = 8 + 26

Combine like terms: 8 + 26 = 34

34x = 34

Divide each side by '34'.

x = 1

Simplifying

x = 1

MARK AS BRAINLIST

IF IT IS HELPFUL THANK MY ANSWER

Answered by sagnik124832
1

Answer:

34/-15

Step-by-step explanation:

17(2-x) - 5(x+12) = 8/1 - 7x

=> 34 - 17x - 5x - 60 = 8 - 7x

=> -26 - 22x = 8 - 7x

=> - 22x + 7x = 8 + 26

=> -15x = 34

=> x = 34/-15

Similar questions